The influence of Solesmes on the Theory of Dom Hans van der Laan OSB on Liturgy and Architecture - Remery, Michel (Jaarboek voor liturgieonderzoek, 2010)
The Dutch Benedictine monk and architect Dom Hans van der Laan OSB (1904-1991) holds an extraordinary position among theoreticians in the fields of both liturgy and architecture even today.1 His theory connects these two subjects in an ingenious manner. He has developed this theory in more detail than many other scholars in the field.